2022
DOI: 10.3389/fpsyt.2022.843088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Perception and Treatment Options for Behavioral and Psychological Symptoms of Dementia (BPSD) in Italy

Abstract: BackgroundBehavioral and psychological symptoms of dementia (BPSD) have a high prevalence, and their presence is associated with a severe impact in terms of social costs. However, dedicated clinical tools or biomarkers to detect these symptoms are lacking. Thus, BPSD management in clinical settings is challenging. The aim of this study was to investigate the perception and the treatment strategies for BPSD in Italian centers working in the dementia field.MethodsA multicenter, national survey was developed by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A few BPSD also have been included in the diagnostic criteria of specific dementias (Rascovsky et al, 2011 ; McKeith et al, 2017 ), and they are already frequently found in the prodromal phases (Pocnet et al, 2015 ; Van der Mussele et al, 2015 ; Wiels et al, 2021 ), sometimes even being the main presenting symptom in the preclinical condition called mild behavioral impairment (MBI) (Creese and Ismail, 2022 ). Various attempts have been made to cluster them into broader categories, such as psychosis, affective syndrome, apathy, mania, and psychomotor syndrome, but a consensus on the topic is lacking (D'antonio et al, 2022 ). Perhaps due to their elusive nature in terms of both definition and rigorous assessment, these non-cognitive symptoms, in spite of their enormous prevalence, have often been overshadowed by the various sets of diagnostic criteria for dementia syndrome, in general, and Alzheimer's disease, in particular, both of which mainly focus on the cognitive aspects of the two conditions (Gottesman and Stern, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few BPSD also have been included in the diagnostic criteria of specific dementias (Rascovsky et al, 2011 ; McKeith et al, 2017 ), and they are already frequently found in the prodromal phases (Pocnet et al, 2015 ; Van der Mussele et al, 2015 ; Wiels et al, 2021 ), sometimes even being the main presenting symptom in the preclinical condition called mild behavioral impairment (MBI) (Creese and Ismail, 2022 ). Various attempts have been made to cluster them into broader categories, such as psychosis, affective syndrome, apathy, mania, and psychomotor syndrome, but a consensus on the topic is lacking (D'antonio et al, 2022 ). Perhaps due to their elusive nature in terms of both definition and rigorous assessment, these non-cognitive symptoms, in spite of their enormous prevalence, have often been overshadowed by the various sets of diagnostic criteria for dementia syndrome, in general, and Alzheimer's disease, in particular, both of which mainly focus on the cognitive aspects of the two conditions (Gottesman and Stern, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The behavioral and psychological symptoms of dementia (BPSD) are a heterogeneous set of psychological reactions, psychiatric symptoms, and behavioral abnormalities that are present in persons with dementia (PwD) due to any etiology (D'antonio et al, 2022 ). These have been grouped in different clusters across different studies.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common classifications divides them into five clusters: psychosis (delusions and hallucinations), affective symptoms (anxiety and depression), apathy, psychomotor symptoms (irritability, aberrant motor behaviors, agitation), and mania (euphoria and disinhibition). In Italy, the most common BPSD seem to be agitation, apathy, depression, psychosis, and aggression (D'antonio et al, 2022 ). It is likely that cultural and ethnic differences might partially explain the heterogeneity and relevance of BPSD across different countries and settings, as well as caregivers' responses (Abe et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations